Uso de las herramientas tecnológicas y su incidencia en el proceso de enseñanza - aprendizaje en los estudiantes de la Unidad Educativa Eugenio Espejo - periodo lectivo 2021-2022 - Herrera Montoya, Gilson Jose (2022)
The importance of this project focuses on technological tools in the teaching-learning process of the "Eugenio Espejo Educational Unit", so that the class hours can contribute to the development of skills and abilities in students. The theoretical foundations referring to the two variables were extracted, which were detailed in detail. Given that we currently face a digital age with technological advances that influence different social areas, the relevance of improvements in the educational field must go hand in hand with the various existing technological tools that benefit the teaching-learning process, making it more attractive, accessible and pleasant for students. The relevance of an education based on the use of technological resources today is not an option but rather a common duty that each educational institution must implement. Similarly, the teaching commitment to update and innovate to be at the forefront of today is important since they are in charge of educating future generations, making use of existing modern tools. This study analyzes the benefits generated by the use of technological tools in terms of student motivation, which is why it should start from a problem analyzed and found in the educational institutions later mentioned as the main object of this qualitative research.